Pengaruh tangibility, profitability, liquidity, firm size dan non debt taxshield terhadap capital structure pada sektor pertanian - DEDE BADRU TAMAM; SATRIYO WIBOWO (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2017)
The purpose of this research is to test and analyze empirically the influence of tangibility, profitability, liquidity, firm size and non-debt tax shield toward capital structure. The object of this research is agriculture sector companies that listed in Indonesia Stock Exchange period 2008-2014. The purposive sampling is used as sampling technique, where 14 companies met the criteria and were analyzed using eviews 8 panel data regressions with random effect model to test the hypothesis. The results of this research shows that liquidity and firm size influence capital structure, while profitability, tangibility and non-debt tax shield do not influence capital structure.